(-1)³-(-1)∧4 +(-2)²-2³+(-1-1)²
Soluções para a tarefa
Respondido por
1
(-1)³-(-1)∧4 +(-2)²-2³+(-1-1)²=
(-1)-(1)+(4)-8+(-2)²=
-1-1+4-8+4=
-2+8-8=
-2
(-1)-(1)+(4)-8+(-2)²=
-1-1+4-8+4=
-2+8-8=
-2
Respondido por
0
(-1)³-(-1)∧4 +(-2)²-2³+(-1-1)²=
eliminando as potencias ( passando negativos para positivos na potencia)
1-1 +4 -8+4
-1-1 ( +4+4 subtraindo com o - 8 = 0)
resultado = - 2
eliminando as potencias ( passando negativos para positivos na potencia)
1-1 +4 -8+4
-1-1 ( +4+4 subtraindo com o - 8 = 0)
resultado = - 2
Perguntas interessantes